Faktor Pendorong Satisfaction: Studi Peran Perceived Value, Perceived Price, dan Electronic Word of Mouth - Anisa Cahyani; Puji Astuti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Various marketplace sites have sprung up on digital platforms, such as Shopee, Tokopedia, Lazada, and others. The purpose of this study is to further explore the extent of the relationship between Perceived Value, Perceived Price, E-WOM, and Perceived Convenience which can increase Satisfaction on Repurchase Intention. This research uses a quantitative approach with a survey design through a Google Form questionnaire to 298 Shopee, Tokopedia, and Lazada users in Jabodetabek, with data analysis using Structural Equation Modeling (SEM) Lisrel. This study changed the Trust variable to Perceived Price and added the Satisfaction variable as a factor in business success. This study shows that Perceived Convenience and Perceived Value have no relationship to Repurchase Intention, while Perceived Price increases Perceived Value. Perceived Value also has a positive effect on E-WOM and Satisfaction, which can encourage consumers to recommend products and repurchase intentions. These findings emphasize the importance of product quality, competitive pricing strategies, and efforts to increase E-WOM to strengthen customer satisfaction and repurchase intentions. Future research is expected to use more specific respondents with different measurement techniques, for example by conducting cross-country or even cross-region so that the data obtained is as needed and as expected.